2017
DOI: 10.4103/ijcm.ijcm_266_15
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress among higher secondary school students of Imphal, Manipur

Abstract: Introduction:Adolescence is a stressful period due to physical, psychological, sexual changes, and the presence of psychiatric disorders such as depression, anxiety, and stress at this stage of life is a matter of concern.Objectives:The objectives of the study were to determine the prevalences of depression, anxiety, and stress among higher secondary school students of Imphal and to determine the association between depression, anxiety, and stress and selected variables such as gender, standard, and religion.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 24 publications
9
41
5
Order By: Relevance
“…Their study also found a significantly higher prevalence of depression and stress among 12 th class students. 3 The current study has identified higher prevalence of depression, anxiety, and stress (73.5%, 86.5% and 24.7%) when compared with their study and also showed a higher prevalence of stress among males and higher level of depression, anxiety, and stress among 10 th class students.…”
Section: Discussionsupporting
confidence: 50%
“…Their study also found a significantly higher prevalence of depression and stress among 12 th class students. 3 The current study has identified higher prevalence of depression, anxiety, and stress (73.5%, 86.5% and 24.7%) when compared with their study and also showed a higher prevalence of stress among males and higher level of depression, anxiety, and stress among 10 th class students.…”
Section: Discussionsupporting
confidence: 50%
“…This was comparable to the study conducted at Imphal, Manipur where the prevalence rate was 19.5%. 15 Indian studies have shown prevalence ranging from 18.4% to 38%. [16][17][18] A study conducted by Russell P et al found the prevalence of depression to be 13.9%.…”
Section: Discussionmentioning
confidence: 99%
“…12 th class students had more significantly prevalence than other class students. 7 Offord et al studied children at ages of 4-16 years for prevalence of emotional disorder, conduct disorder, somatization and hyperactivity. Overall combined prevalence was found to be 18.1%.…”
Section: Discussionmentioning
confidence: 99%